The Influence of The Quality of Financial Reports of Muslim Religious Institutions on Stakeholder Satisfaction in Riau - Saputra, Wali (JAF (Journal of Accounting and Finance), 2024)
This study aims to analyze the influence of the quality of the financial reports of Muslim religious institutions in Riau on stakeholder satisfaction. This study uses primary data obtained by distributing questionnaires to 204 stakeholders who always interact and are active in Muslim religious institutions. Data analysis methods used in this study include research instrument testing and hypothesis testing using regression analysis. The results of the study show that the quality of the financial reports of Muslim religious institutions has an effect on stakeholder satisfaction.Keyword: Quality of Financial Statements; Muslim Religious Institutions; Stakeholder Satisfaction. Keywords: Quality of Financial Statements, Muslim Religious Institutions, Stakeholder Satisfaction